2017
DOI: 10.1007/s11356-017-9930-4
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity variability and metal accumulation strategies in plants spontaneously inhibiting fly ash lagoon, India

Abstract: Out of 29 plant species taken into consideration for biodiversity investigations, the present study screened out Cyperus rotundus L., Calotropis procera (Aiton) W.T. Aiton, Croton bonplandianus Baill., Eclipta prostrata (L.) L., and Vernonia cinerea (L.) Less. as the most suitable metal-tolerant plant species (high relative density and frequency) which can grow on metal-laden fly ash (FA) lagoon. Total (aqua-regia), residual (HNO) and plant available (CaCl) metal concentrations were assessed for the clean-up o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 50 publications
4
12
0
2
Order By: Relevance
“…Similarly, Roca et al [116] showed that the extractable fraction of metals in soils can be related to the bioaccumulation factor for the identification of native plants with the capacity to take up high concentrations of metals from soils and accumulate them in their tissues. Other studies have also shown that soil available metal concentration is the most appropriate basis for examining plant metal uptake [117][118][119][120][121]. Thus, we conclude that plant available form of metal in soil is a more relevant descriptor than its total form to use in plant-soil metal relationship models.…”
Section: Accepted Manuscriptsupporting
confidence: 50%
“…Similarly, Roca et al [116] showed that the extractable fraction of metals in soils can be related to the bioaccumulation factor for the identification of native plants with the capacity to take up high concentrations of metals from soils and accumulate them in their tissues. Other studies have also shown that soil available metal concentration is the most appropriate basis for examining plant metal uptake [117][118][119][120][121]. Thus, we conclude that plant available form of metal in soil is a more relevant descriptor than its total form to use in plant-soil metal relationship models.…”
Section: Accepted Manuscriptsupporting
confidence: 50%
“…(2017) showed that the extractable fraction of metals in soils can be related to the bioaccumulation factor for the identification of native plants with the capacity to take up high concentrations of metals from soils and accumulate them in their tissues. Other studies have also shown that soil available metal concentration is the most appropriate basis for examining plant metal uptake (Jamali et al, 2006, Massas et al, 2013, Wójcik et al, 2014, Mukhopadhyay et al, 2017. Thus, we conclude that plant available form of metal in soil is a more relevant descriptor than its total form to use in plant-soil metal relationship models.…”
Section: Conceptual Framework Validation Using Field Survey Of Queenssupporting
confidence: 49%
“…where n i is the number of individuals of each species; N the total number of individuals To quantify species biodiversity, the Shannon-Wiener Diversity Index (H) was calculated (Mukhopadhyay et al 2017):…”
Section: Biodiversity and Dominance Assessmentmentioning
confidence: 99%